TOLERANSI BERAGAMA DALAM PERSPEKTIF HAM DI INDONESIA - Febri Handayani (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2010)
In the reform era, the diversity of the sociely tend to be a burden on the nations capital of Indonesia. This was evidenced by the emergence of various issues problems associated with the diversity of sources, particularly the field of religion. In a religious perspective, there is some opinion states that all religious groups do not convinced that the basic values of each religion is tolerance. As a result, which appears intolerance and conflict. throught religion can be a positive energy to build a tolerance value in order to realize a just and prosperous country, as mandated by the Constitution 1945.this is proven by the human rights guarantees against someone, especially in terms of religion, religious tolerance with the aim to run well